Kajian Nilai Nilai Kemanusiaan Pada Upacara Nyulubang/Mekingsan (Studii Kasus di Kabupaten Mesuji, Provinsi Lampung) - Putu Panila Saputra; I Ketut Budiawan; Anak Agung Oka Puspa (Sekolah Tinggi Agama Hindu Dharma Nusantara Jakarta, 2022)
This study discusses: Study of Human Values at the Nyulubang Ceremony in Mesuji Regency, Lampung Province. The Nyulubang or Mekingsan ceremony in Mesuji Regency is very important to study because it is carried out from generation to generation but not many understand its function, and meaning, but in general people believe there will be impacts if the tradition is violated. the meanings and values of humanity that are written and implied in it. In general, this study aims to describe the data and facts that occur in the field so that it is expected to be a guide and provide guidance to the public in order to know how the procession of the Nyulubang Mekingsan Ceremony in Mesuji Regency, Lampung Province; This study uses qualitative research methods to systematically obtain data, determine data sources, data processing, and data analysis so that it can be understood about the Human Values at the Nyulubang Ceremony in Mesuji Regency, Lampung Province. The results of this study reveal that the Nyulubang/Mekingsan ceremony is carried out by Hindus in Mesuji Regency, Lampung Province, because there is no good day to carry out the pitra Yadnya ceremony (burying the corpse carrying out the Pengabenan Ceremony). The Nyulubang/Mekingsan ceremony is a procession of burying corpses carried out by Hindus in Mesuji Regency, Lampung Province secretly (not reporting to Kelian Adat, Parisada, and other Village Officials, therefore the implementation is only attended by the closest family). The purpose of carrying out the Nyulubang / Mekingsan Ceremony is so that the body is not long left in the house. The human values contained in the Nyulubang/Mekingsan ceremony are the values of compassion, non-violence, the value of peace, the right attitude, and the truth.